Classification and occurrence of defective acts in residential construction projects - Aljassmi, Hamad A.; Han, Sangwon (Journal of Civil Engineering and Management, 2014)
Defects can have a significant impact on construction performance. Numerous studies have attempted to identify their root causes, contending that the prevention of defects could be achieved by eliminating the root causes. Yet, their direct causes also need to be considered in order to identify the sequence of events leading to defects. This study aims to classify the defective acts that are directly linked to the occurrence of a defect, in order to provide insights about the nature and the impact of different types of direct causes. The study involves investigation into 272 defects from 81 disputes that occurred in the Dubai residential construction industry in 2009. Results from this study reveal that the majority of construction defects are driven by a violation of practices or workers’ lack of skill and competence. While it is difficult to prevent deliberate violations, increased effort toward growing skills and competencies would be effective in reducing defects, and therefore improving construction performance. Also, classification of defective acts is envisioned as a platform toward a more thorough causal tracking of construction defects, facilitating the identification of latent conditions resulting in defects.